Pengaruh Pendekatan Accelerated Learning terhadap Kemampuan Pemecahan Masalah Matematis - Qomario Qomario (Journal of Elementary School (JOES), 2018)
The aim of the study was to know the effect of accelerated learning on mathematics problem solving. This was a quasi experimental study. The subject was class VA and VB. The hyphotesis testing used t test calculation. The result was ttest result = 3,071 and ttabel = 2,001, because tobtain > ttable so that H0 was rejected and H1 was accepted. Tjerefor, it can be concluded that accelerated learning was significantly influence in improving students mathematics problem solving. Keywords: Accelerated Learning Approach, Mathematics Solving Problems